POLICY AVAILABLE AND SUSTAINABLE WATERFRONT DEVELOPMENT - Md. Yassin, Azlina; Masrom, Md. Asrul Nasid; Mohd. Razali, Mohd. Najib; Mohd. Adnan, Yasmin (PLANNING MALAYSIA, 2018)
Waterfront redevelopment emerged in the 1970s. Since then, numerous waterfront areas went through transitions from abandoned spaces to commercial, residential and recreational areas. The transformation symbolizes the independent city states’ efforts to remake themselves for the 21st century. However, due to constraints such as ineffective governance as well as inadequate federal, state and municipal planning guidelines, the waterfronts faced problems such as environmental degradation, crime and flooding. Although some waterfront development projects remained profitable due to good public access, many did not. This paper intends to identify and evaluate the current regulations and guidelines towards sustainable waterfront development in Malaysia. The findings were based on the questionnaires mailed and e-mailed to property development companies listed under Bursa Malaysia in Malaysia. The findings identified ten laws and regulations related to waterfront development in Malaysia such as; the National Land Code 1965, the Town and Country Planning Act 1976, and the Environment Quality Act 1974. In terms of the sufficiency of those regulations and guidelines for controlling waterfront development, more than half of respondents claimed that Malaysia did not have sufficient regulations to control waterfront development and the regulations were weakly enforced in Malaysia. The findings indicated that the government and the policy makers need to improve regulations for waterfront development.